Where Have We Got To? Stories of Survival, Resistance and Retreat in Sustaining Commitment to Social Purpose in Adult Education - Paul Armstrong (Adult Education Research Conference, 2004)
As part of a larger study seeking to understand the social, political and cultural values of those who began teaching adult education between 1975 and 1985, this focuses on those adult educators from North America and the UK who took part in an Exchange program between 1984 and 1988.